2023
DOI: 10.1007/s00018-023-04776-x
|View full text |Cite
|
Sign up to set email alerts
|

eEF2 improves dense connective tissue repair and healing outcome by regulating cellular death, autophagy, apoptosis, proliferation and migration

Abstract: Outcomes following human dense connective tissue (DCT) repair are often variable and suboptimal, resulting in compromised function and development of chronic painful degenerative diseases. Moreover, biomarkers and mechanisms that guide good clinical outcomes after DCT injuries are mostly unknown. Here, we characterize the proteomic landscape of DCT repair following human Achilles tendon rupture and its association with long-term patient-reported outcomes. Moreover, the potential regulatory mechanisms of releva… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…CircEEF2 also contributes to autophagy by inhibiting the mTOR pathway and upregulating the expression of autophagy-related gene 5 (ATG5) and ATG7 ( Yong et al, 2020 ). Regarding tissue repair, activation of EEF2 was observed to reduce apoptosis and enhance the recovery of dense connective tissue ( Chen et al, 2023 ) by promoting autophagic flux ( Pires Da Silva et al, 2020 ). Fibroblasts are the critical effector cells in RA ( Bartok and Firestein, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…CircEEF2 also contributes to autophagy by inhibiting the mTOR pathway and upregulating the expression of autophagy-related gene 5 (ATG5) and ATG7 ( Yong et al, 2020 ). Regarding tissue repair, activation of EEF2 was observed to reduce apoptosis and enhance the recovery of dense connective tissue ( Chen et al, 2023 ) by promoting autophagic flux ( Pires Da Silva et al, 2020 ). Fibroblasts are the critical effector cells in RA ( Bartok and Firestein, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is a close relationship between autophagy and tissue repair. 41 Briefly, autophagy participates in the clearance of intracellular waste and the recycling of metabolic products, which can provide necessary nutrients for damaged tissues and promote tissue repair. 42 Ma and colleagues have found that inducing autophagy leads to more labeled MSCs migrating to the site of injury.…”
Section: Discussionmentioning
confidence: 99%
“…Rosavin thus influences the inhibition of the deacetylation process of EEF2 [44]. EEF2, in turn, under physiological conditions, is responsible for bone formation processes and is postulated to have an anti-osteoporotic effect [46,48]. In a dedicated study on the HDAC1/EEF2 axis, it was observed that rosavin reduced the levels of RANKL, M-CSF, and TRAP in the blood serum of OVX mice [44].…”
Section: Impact Of Rosavin On Bone Tissue Metabolismmentioning
confidence: 99%